Carbon Monoxide Stimulates Chondrocyte Mitochondria and Protects Mitochondria During Cartilage Injury - Suryamin Liman; Madeline R. Hines; Piedad C. Gómez-Contreras; Emily Witt; Jacob S. Fisher; Kevin J. Lu; Lauren D. McNally; Alicia T. Cotoia; Maxwell Y. Sakyi; Brett A. Wagner; Michael S. Tift; Douglas Fredericks; et al. (Antioxidants)
Objective: Joint injury precipitates post-traumatic osteoarthritis (PTOA) via chondrocyte mitochondrial oxidative damage. Carbon monoxide (CO) is a small molecule with potent antioxidant and mitochondrial benefits in other tissues that have not been explored in healthy chondrocytes. We hypothesized that CO would subvert the mitochondrial effects of articular cartilage injuries upon resident chondrocytes. Design: We evaluated intra-articular delivery of a novel carbon monoxide-containing foam (COF). We used in vitro impact injuries to explore mitochondrial and redox endpoints after CO exposure. We then applied intra-articular injections of COF or control room air foam (RAF) to assess safety, efficacy, and other intra-articular responses. Results: COF increased the expression of HO1 and mitofusin-1 within 1 h and this increase was sustained for 12 h in vitro. COF increased chondrocyte mitochondrial respiration by 40% and increased reduced (not oxidized) thiols by 50% following in vitro injury to osteochondral explants. After cartilage injury, COF prevented the formation of 3-nitrotyrosine and the loss of articular chondrocyte mitochondria. When injected intra-articularly, COF was retained for 24 h post-injection in mouse stifle joints. It increased HO1 in those joints, enhanced reduced thiol levels in rabbit stifle joints, and exhibited no toxicity 1 and 4 weeks after injection. Conclusions: This study supports the hypothesis that CO functions as an antioxidant for articular chondrocytes by supporting mitochondria and intracellular GSH in the presence or absence of cartilage injury. Challenges in delivering exogenous CO have limited its preclinical development, but new CO-releasing materials like COF may enable new examinations of this promising small molecule.